The Analysis of 4C-Based Learning Implementation for Islamic Religious Education Students - Destriani; Idi Warsah; Asri Karolina; Sutarto; Gerard Krzic ‎ (TADRIS: Jurnal Pendidikan Islam, 2024)
The purpose of this study is to identify issues surrounding the application of 4C-based learning. In addition, this study looks at how lecturers address issues that arise with their pupils. The method used in this study is qualitative descriptive. Purposive sampling procedures were used in the selection of the 20 students and 2 lecturers participated in this study. Data were gathered by open-ended surveys, interviews, and observations. Data analysis involves gathering, condensing, presenting, and deriving conclusions using interactive models. Researchers found that lecturers tried to engage 4C based learning during their class. The necessary abilities, which include the capacity for critical and creative thought as well as collaboration and communication, must be tailored to the trends of the twenty-first century. Students’ abilities to argue critically with others and to articulate their thoughts rationally serve as examples of this. Besides, students are able to exhibit their capacity for productive work, recognize the diversity within the team, show adaptability and a readiness to consider other people’s viewpoints, assume joint accountability for group projects, and recognize the significance of each team member’s contribution to a diverse group. They consider some applications such as Canva, Mind Master, Kahoot, and QR Code for their creativity supports. As well as, writing papers assignment is able to build studentsâ€™ critical thinking skills. Students who possess critical thinking abilities may identify issues, come up with solutions, and gather and arrange data. Studentsâ€™’ ability to create topic papers and research papers serves as evidence of this.